Clinical Performance of Nonvitamin K Antagonist Oral Anticoagulants in Real-World Obese Patients with Atrial Fibrillation - Russo, Vincenzo; Bottino, Roberta; Rago, Anna; Papa, Andrea Antonio; Liccardo, Biagio; D'Onofrio, Antonio; Golino, Paolo; Nigro, Gerardo (Seminars in Thrombosis and Hemostasis, 2020)
The prevalence of both atrial fibrillation (AF) and obesity has steadily increased. Nonvitamin K antagonist oral anticoagulants (NOACs) have been shown to be more effective and safer than vitamin K antagonists (VKAs) for long-term stroke prevention in patients with nonvalvular AF. There are still limited data in the literature regarding performance of NOACs in obese patients with AF in the “real world.” The aim of our study was to compare the safety and effectiveness of NOACs versus well-controlled VKA therapy in obese AF patients in a “real-world” setting. Here, we have considered patients with AF and obesity (body mass index [BMI] > 30 kg/m2) on NOAC or VKA therapy included in the multicenter Atrial Fibrillation Research Database (NCT03760874). The occurrence of major bleedings (MBs) and thromboembolic events (composite of ischemic stroke, transient ischemic attack, and systemic embolism) was respectively considered primary safety and effectiveness outcomes. We identified 1,047 AF patients with obesity who received NOAC (n = 272) or VKA (n = 775) treatment. After propensity score matching analysis, 248 NOAC and 496 VKA recipients with similar clinical characteristics, including BMI (34.8 ± 3.4 in NOAC vs. 35.1 ± 3.8 in the VKA group; p = 0.50), were evaluated. The mean follow-up was 39 ± 7 months. The incidence rate of thromboembolic events was 1.10 per 100 person-years (0.67 in NOAC vs. 1.28 in the VKA group; hazard ratio [HR]: 0.52; 95% confidence interval [CI]: 0.22–1.22; p = 0.19). The incidence rate of MB was 1.9 per 100 person-years (1.1 in NOAC vs. 2.28 in the VKA group; HR: 0.46; 95% CI: 0.24–0.88; p = 0.04). The incidence rate of intracranial hemorrhage was 0.4 per 100 person-years (0.27 in NOAC vs. 0.47 in the VKA group; HR: 0.57; 95% CI: 0.12–2.73; p = 0.48). A positive net clinical benefit (NCB) of NOACs over VKAs was found (+0.91). Presence of anemia (HR: 1.75; p = 0.003) and concomitant use of antiplatelet drugs (HR: 2.41; p = 0.001) were found to be independent predictors of MB; moreover, age (HR: 1.65; p = 0.003) was an independent predictor of thromboembolic events. Our data support the hypothesis of safe and effective use of NOACs in patients with AF and obesity, justified by a statistically significant lower incidence of MB and a favorable NCB over VKAs.
Keywords: atrial fibrillation; obesity; NOACs; dabigatran; apixaban; rivaroxaban; edoxaban; bleeding; stroke; embolism